PEMBELAJARAN BERDIFERENSIASI DALAM MENULIS TEKS PROSEDUR SISWA KELAS VII SMP - Andini, Mariani Putri; Rustam, Rustam; Yusra, Hilman; Kamarudin, Kamarudin; Nurfadilah, Nurfadilah (Jurnal Kata : Bahasa, Sastra, dan Pembelajarannya, 2023)
Educators are required to understand the needs of learners according to their interests, talents and aspirations in the current independent curriculum. One of the learning models that focuses on the needs of learners is differentiated learning. This model is a strategy to find out the readiness, interest, and learning profile of students. This study aims to describe the application of differentiated learning in writing procedure text in class VII of SMP Negeri 1 Jambi City. The approach used in this research is descriptive qualitative. The research location was located at SMP Negeri 1 Jambi City. Data were collected through observation, interview, and documentation methods. The results of this study indicate that the implementation of learning to write procedural texts in class VII of SMP Negeri 1 Kota Jambi using differentiated learning is in accordance with the preparation, implementation, and assessment design which contains differentiated content, differentiated process, and differentiated products which means that the learning process focuses on the interests, talents, and learning profiles of students.Keywords: Differentiated learning, writing, procedur text